Two SERK Receptor-Like Kinases Interact with EMS1 to Control Anther Cell Fate Determination. Issue 1 (5th December 2016) - Li, Zhiyong; Wang, Yao; Huang, Jian; Ahsan, Nagib; Biener, Gabriel; Paprocki, Joel; Thelen, Jay J.; Raicu, Valerica; Zhao, Dazhong
Abstract : The Leu-rich repeat receptor-like kinases SERK1 and SERK2 affect anther cell differentiation as a partners of EMS1 in Arabidopsis. Abstract: Cell signaling pathways mediated by leucine-rich repeat receptor-like kinases (LRR-RLKs) are essential for plant growth, development, and defense. The EMS1 (EXCESS MICROSPOROCYTES1) LRR-RLK and its small protein ligand TPD1 (TAPETUM DETERMINANT1) play a fundamental role in somatic and reproductive cell differentiation during early anther development in Arabidopsis ( Arabidopsis thaliana ). However, it is unclear whether other cell surface molecules serve as coregulators of EMS1. Here, we show that SERK1 (SOMATIC EMBRYOGENESIS RECEPTOR-LIKE KINASE1) and SERK2 LRR-RLKs act redundantly as coregulatory and physical partners of EMS1. The SERK1 / 2 genes function in the same genetic pathway as EMS1 in anther development. Bimolecular fluorescence complementation, Förster resonance energy transfer, and coimmunoprecipitation approaches revealed that SERK1 interacted biochemically with EMS1. Transphosphorylation of EMS1 by SERK1 enhances EMS1 kinase activity. Among 12 in vitro autophosphorylation and transphosphorylation sites identified by tandem mass spectrometry, seven of them were found to be critical for EMS1 autophosphorylation activity. Furthermore, complementation test results suggest that phosphorylation of EMS1 is required for its function in anther development. Collectively, these data provide genetic and biochemical evidence of the interaction and phosphorylation between SERK1/2 and EMS1 in anther development.